How successful are men all-around Olympic medalists on apparatus events at Olympic games from 1924 to 2016 - Cuk, I.; Šibanc, K. (Science of Gymnastics Journal, 2018)
At Olympic Games (OG) 1896 in Athens all-around competition in gymnastics was not a discipline. First time all-around title in gymnastics at OG was awarded in Paris in the year of 1900, however there were no apparatus awards given until OG 1924 in Paris. The article shows a historical research and follows development of OG all-around medallists and their success with relation to winning medals on individual apparatus. In Paris1924 Leon Štukelj (Slovenia, ex-Yugoslavia) won all-around and horizontal bar gold medal. Since then all-around medallists shared very different success in apparatus ranking. The last multiple winner was Vitaly Scherbo (Belarus, ex-Soviet Union) who at OG 1992 won all-around and three apparatus finals (rings, vault and parallel bars). Since then such achievement has not been repeated yet. With openended difficulty value in the Code of Points and special competitions held by FIG for apparatus specialist, the doors are opening to more apparatus specialists to attend OG and chances to repeat Scherbo`s success are getting smaller